Effect of cultivation conditions on cellulase activity of higher fungi - Ginterová, A; Janotková, O; Findová, L (Folia microbiologica, 1981)
Production of cellulases was followed in 4 cultures of higher fungi (Agrocybe cylindracea, Len tinus tigrinus, Pleurotus ostreatus, Ramaria formosa) cultivated on various substrates under different conditions. Stationary cultivation was more suitable than the submerged one. Addition of carboxymethy cellulose (CMC) was more suitable than addition of glucose. The cellulase activity in the presence of CMC was higher after a 12-d cultivation than after a 23-d period. Pine sawdust was most effective of all the substrates tested for the production of cellulases. Beech sawdust and wheat or rye straw were also useful. The addition of yeast autolyzate decreased the production of cellulases. A culture of L. tigrinud was the best producer.
Keywords: Cellulase; Carboxymethylcellulose Sodium; sodná sůl karboxymethylcelulosy; Culture Media; glukosa; druhová specificita; Basidiomycota; celulasa; Glucose; Species Specificity; kultivační média